New Closed Sets and Maps via Ideals: Ramandeep Kaur, Asha Gupta - Team, Support (Thai Journal of Mathematics, 2017)
The purpose of this paper is to study a new class of closed sets, called generalized semi-closed sets with respect to an ideal, which is an extension of generalized semi closed sets. Then, by using these sets, we introduce the concept of Igs-compact spaces along with some new classes of maps via ideals and obtain analogues of some known results for compact spaces, continuous maps and closed maps in general topology.